Task allocation and scheduling system - Thai, Wei Cheng (Nanyang Technological University, 2023)
In the School of Computer Science and Engineering (SCSE) at Nanyang Technological University (NTU), a previous Final Year Project student created a web-based application called Timetable Planning and Scheduling system (TPS) for planning and scheduling classes in SCSE. But due to the lack of maintenance and update of the application, bugs and security issues have occurred. This project aims to resolve this by completely rebuilding the whole application from the ground up with modern technologies. This paper will present the research done of the different technologies available in 2023. It will also discuss the system design of the application, the features that have been implemented and future improvements to the application.